Heritage value of the traditional Malay villages as protected landscapes / Kamarul Bahrain Shuib and Habsah Hashim - Shuib, Kamarul Bahrain; Hashim, Habsah (2015)
In Malaysia, environments such as the rural countryside that are characterized by paddy fields, fruit orchards, rustic villages, forests, river banks and coastal plains are slowly being transformed and converted to other land uses. The general public awareness on the heritage value of such environment is very low and disappointing. Governmental authorities, land owners and developers view these environments as areas potential for future development, without much consideration into their historical and heritage values. These rural landscapes form part of the national landscape character in many districts in peninsular Malaysia. As such the purpose of this paper is to highlight the importance of the traditional rural Malay villages as cultural landscapes that are worthy of preserving. Protecting these cultural landscapes is crucial before more and more of such areas being lost to give way to urban types of development. Using the Landscape Value Method, the three case study examples from the district of Kuala Muda in the state of Kedah, district of Kerian and sub-district of Lenggong in the state of Perak provide sufficient evidence on the importance of preserving these traditional Malay rural environments. This paper concludes with some measures to preserve the rural Malay heritage as IUCN’s Category V (protected landscapes).